From Norvelt to nowhere - Gantos, Jack (Square Fish, 2015)
After an explosion, a new crime by an old murderer, and the sad passing of the founder of Norvelt, Pennsylvania, twelve-year-old Jack accompanies his slightly mental elderly mentor, Miss Volker, on a cross-country run as she pursues the oddest of outlaws.